计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 06:14:49
计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)计算

计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)
计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)

计算1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)
1/x(x+4)+1/(x+4)(x+8)+1/(x+8)(x+12)=x-3/x(x+12)
4/x(x+4)+4/(x+4)(x+8)+4/(x+8)(x+12)=4(x-3)/x(x+12)
1/x-1/(x+4)+1/(x+4)-1/(x+8)+1/(x+8)-1/(x+12)=4(x-3)/x(x+12)
1/x-1/(x+12)=4(x-3)/x(x+12)
x+12-x=4x-12
x=6
检验:x=6是方程的解